Modeling of the outflow of an ideal fluid from the tank bottom - Averkova, O.A.; Logachev, I.N.; Logachev, K.I.; Khodakov, I.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2014)
The problem of outflow of an ideal incompressible fluid from a tank is considered for the case when the tank bottom is of a stepwise shape. The Zhukovskii method and the Maple system are used to construct equipotential grids and streamlines. The variation regularities are studied for the slope angle and compression coefficient of the fluid jet in relation to the domain geometry. Using the stationary discrete vortices, a numerical scheme for determining the outflow properties of such jets is proposed. The adequacy of the proposed approach to the numerical modeling of jet flows from vessels is confirmed by a comparative analysis of numerical results.